Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

"Metal-free'' synthesis of 1,2,3-triazoles via tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of ethyl acrylate derivatives - Kumar, B. Senthil; Gadakh, Sunita; Sudalai, Arumugam (Tetrahedron Letters, 2018)
An efficient ``one-pot'' method for the synthesis of substituted 1,2,3-triazole derivatives in excellent yields as single regioisomer is reported. The key transformation involves an atom-efficient tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of acrylate derivatives on treatment with NaN3 in DMF under mild conditions. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Intramolecular cycloaddition; Regioselective; Tandem azidation; triazoles

Enolate-mediated regioselective synthesis of 1,2,3-triazoles via azide-aldehydes or ketones [3+2]-cycloaddition reactions in aqueous phase - Tripathi, Anupam; Rode, V, Chandrashekhar; Llop, Jordi; Chavan, Subhash P.; Joshi, Sameer M. (Tetrahedron Letters, 2020)
A synthetic route for the direct conversion of arylazides into the corresponding trizoles via phase transfer catalyst-assisted [3+2] cycloaddition reaction under basic conditions in aqueous medium is reported. This synthetic methodology, which offers high yields and excellent regioselectivity for varieties of triazoles at 100 degrees C for 24 h-48 h and this `greener' synthesis constitutes an alternative to the previously reported well established click reactions. Published by Elsevier Ltd.
Keywords: Azides plus aldehydes or ketones; Click chemistry; triazoles; Water